Investigating the Use of Research Software by Postgraduates in Computer Science - Shigihara, Yukio; Mourão, Érica; Viterbo, José; Vasconcelos, Leonardo (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
This article investigates the challenges and benefits associated with the use of research software by master’s and doctoral graduate students in Computer Science. The study was conducted through a survey with 186 respondents, involving quantitative and qualitative data analysis. The results highlight difficulties related to the complexity of the tools, the learning curve, and integration with academic workflows. The research offers practical support for developers, institutions, and researchers, aiming at a more effective adoption of these technologies in the academic context.